Optimization of a PID Controller for a Single-Link Robotic Arm Using a Genetic Algorithm (The International Journal of Engineering & Information Technology (IJEIT), 2025)
This paper investigates the application of a Genetic Algorithm (GA) to optimize the parameters (Kp, Ki, Kd)  of a Proportional-Integral-Derivative (PID) controller for a single-link robotic arm. The objective is to minimize key performance metrics such as settling time, overshoot, and steady-state error. A simplified dynamic model of the robotic arm is used for simulation. The GA is implemented with roulette wheel selection, single-point crossover, and Gaussian mutation. Simulation results demonstrate the effectiveness of the GA in automatically tuning the PID controller, achieving significant improvements in transient and steady-state response.